EURECA - Kraus, H; Brown, A; Coulter, P; Henry, S; Ingleby, S; Mikhailik, V; Sullivan, P; Pari, P; Armengaud, E; Domange, J; Gerbier, G; Graffin, P; et al. (2010)
EURECA (European Underground Rare Event Calorimeter Array) is an astro-particle physics facility aiming to directly detect galactic dark matter. The Laboratoire Souterrain de Modane has been selected as host laboratory. The EURECA collaboration unites CRESST, EDELWEISS and the Spanish-French experiment ROSEBUD, thus concentrating and focussing effort on cryogenic detector research in Europe into a single facility. EURECA will use a target mass of up to one ton, enough to explore WIMP - nucleon scalar scattering cross sections in the region of 10 - 10 picobarn. A major advantage of EURECA is the planned use of more than just one target material (multi target experiment for WIMP identification). © Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.